2010
DOI: 10.1039/c0cc02357d
|View full text |Cite
|
Sign up to set email alerts
|

Gold(i)/Zn(ii) catalyzed tandem hydroamination/annulation reaction of 4-yne-nitriles

Abstract: The tandem hydroamination-annulation reaction of 4-pentynenitriles in the presence of amine nucleophiles and a cooperatively operating catalyst system, consisting of Ph 3 PAuCl and Zn(ClO 4 ) 2 , provides an efficient route to 2-aminopyrroles. Two regioisomeric 2-aminopyrroles were formed in moderate to good yields.Over the past six years, gold catalysis has shown to be a powerful tool in organic synthesis. Cationic gold(I) and gold(III) complexes show unique behavior towards unactivated alkenes, alkynes, alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…Spiroketals 65 and fused tricyclic compounds 67 are also accessible from similar alkyne hydrofunctionalisation/cycloaddition sequences, where the Lewis acid also acts to generate ortho-quinonemethides from 2-(hydromethyl)phenol derivatives. Au and Lewis acid-catalysed alkyne hydroamination has also been applied to the synthesis of N-heterocycles such as a pyrroles 68 and indoles. 69 Lewis acids can also affect Au-mediated steps of the catalytic reaction.…”
Section: Au and Lewis Acid Tandem Catalysismentioning
confidence: 99%
“…Spiroketals 65 and fused tricyclic compounds 67 are also accessible from similar alkyne hydrofunctionalisation/cycloaddition sequences, where the Lewis acid also acts to generate ortho-quinonemethides from 2-(hydromethyl)phenol derivatives. Au and Lewis acid-catalysed alkyne hydroamination has also been applied to the synthesis of N-heterocycles such as a pyrroles 68 and indoles. 69 Lewis acids can also affect Au-mediated steps of the catalytic reaction.…”
Section: Au and Lewis Acid Tandem Catalysismentioning
confidence: 99%
“…In 2010, Demir et al [50] successfully developed a 4-amine 24 (Scheme 30) cyclochemistry catalyzed by Au(I)/Zn(II) in series as well. An effective, versatile and widely available synthetic pyrrole with multiple substituents is provided.…”
Section: The Effects Of Different Compounds Containing N–hmentioning
confidence: 99%
“…The authors suggested that the Zn catalyst was responsible for the hydroamination of the nitrile, while the Au catalyst activated the alkyne for pyrrole formation. Mixtures of 2‐amino‐ and 2‐alkylaminopyrroles 156/157 were obtained in 13–81% yield 110…”
Section: N‐nucleophilesmentioning
confidence: 99%